Evaluation for solid wastes disposal site using geographic information system in Phu Wiang district cluster Khon Kaen province - Ayuwat Thanasate-angkool (Chulalongkorn University, 2010)
Thesis (M.Sc.)--Chulalongkorn University, 2006